THE EFFECTIVENESS OF CHARACTER EDUCATION MODEL BASED ON REGIONAL DANCE ARTS TO SUPPORT CHILD FRIENDLY SCHOOL - Siti Supeni; Setyasih Harini; Inggis Mialiawati (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The research aims at testing the effectiveness of developmental model of character education based on regional art dance at child friendly school in Surakarta viewed from education, recreation, and competitive and finding out the implementation of character education based on regional dance through developmental model of character education at child friendly school based on regional culture (being able to be used as regional tourism assets). The methods of research are literature studies, interview, survey, observation, and documentation. The data were analyzed through research and development (R&D).The research findings show that the implementation of regional art dance in character education achieve 80 % up to 100% because art dance has been programmed at elementary school in Surakarta to support cultural village; however in the implementation of child friendly school is to ask a question to regional government for its policy for developing art dance through character education model stating that there are 66.7 % of respondents do not understand about the model; therefore it needs to continue with a socialization model. Keywords: character education, child friendly school, regional dance